Rotation sensing with Er3+-doped active ring resonator slow light structure. Issue 19 (27th October 2016) - Gu, Hong; Liu, Xiaoqin
Abstract: An optical gyroscope, which is constituted by Er 3+ -doped active ring resonator (EDARR) slow light structure, is presented for the first time. The principle of improving the sensitivity of the detection of angular velocity is analysed in detail. The expression of the rotation phase difference of EDARR between the counter-propagating waves is derived and discussed. At the resonant frequency, the phase shift difference has the maximum value when the light power in the cavity is far greater than the input light power. We designed an experimental scheme of Er 3+ -doped active ring resonator slow light system. Two additional bias phases ϕ b = ± π /2 were introduced in the optical path, by recording the light intensity difference Δ I ( ω 0 ) and I 0 at the resonant frequency ω 0, the input angular velocity can be obtained. The slow light structure based on EDARR can enhance the sensitivity of the detection of the angular velocity by three orders of magnitude.